Rescues - Brian, Janeen; Brian, Janeen Janeen Margaret; Era Publications (Flinders Park, South Australia Era Publications, 1993)
An engaging introduction to various rescue operations, including sea, mountain, and fire rescues, designed for primary school students.
Includes bibliographical references.
Primary school students
Keywords: Rescue work